Constraining speleothem oxygen isotope disequilibrium driven by rapid CO2 degassing and calcite precipitation: Insights from monitoring and modeling. (1st September 2020) - Carlson, Peter E.; Noronha, Alexandra L.; Banner, Jay L.; Jenson, John W.; Moore, Mark W.; Partin, Judson W.; Deininger, Michael; Breecker, Daniel O.; Bautista, Kaylyn K.
Abstract: Oxygen isotopes are the most commonly applied speleothem proxy for reconstructing Quaternary changes in precipitation and/or temperature. These interpretations are either limited to qualitative wetting and drying trends or rely on theoretical, experimental and/or empirical equilibrium isotope fractionation factors for more quantitative constraints. These various fractionation factors have similar temperature sensitivities, but their absolute values differ, and cave calcite does not appear to generally precipitate in isotopic equilibrium with its drip water. Rapid CO2 degassing paired with calcite precipitation, both occurring under disequilibrium conditions, are a set of mechanisms commonly invoked to explain offsets between observed and equilibrium isotopic fractionation between cave calcites and drip waters. However, the relevance of these disequilibrium mechanisms to speleothem records remains unresolved. Here, we compare measured δ 18 O values of modern speleothem calcite from a tropical cave in Guam to calcite δ 18 O values predicted by a modified version of the ISOLUTION proxy system model. This extends the global comparison of cave drip water and modern calcite δ 18 O values to higher temperatures. We initialize the model using contemporaneous measurements of drip water (δ 18 O values, [Ca + ], and pH), and cave air (CO2, and T) from four drip sites over 3.5 years of monitoring in the cave. Through this comparison, we show that for a slow drip-rate site, ventilation-driven CO2 degassing can explain seasonal variations in calcite oxygen isotope composition. At faster-dripping sites in this cave, the seasonal effect is limited. At these sites, the DIC reservoir is replenished by new drips faster than its isotopic composition can be modified by degassing CO2 and calcite precipitation, whether occurring each is occurring as an equilibrium or kinetic process. For the slow drip rate site, however, this is the first observation of cave air CO2 variations exerting a control on cave calcite oxygen isotope values. The confirmation of ventilation-driven processes controlling oxygen isotope values at a slow-drip site advances the process-based understanding of stalagmite formation that is required to move beyond the wetter-or-drier paradigm and make quantitative interpretations of speleothem oxygen isotope records.